The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1518-8345.1310.2790
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of nursing students' learning outcomes through scenario-based skills training

Abstract: Objective: this study analyzed the influence of scenario-based skills training on students' learning skills.Method: the author evaluated the nursing skills laboratory exam papers of 605 sophomores in nursing programs for seven years. The study determined the common mistakes of students and the laboratory work was designed in a scenario-based format. The effectiveness of this method was evaluated by assessing the number of errors the students committed and their achievement scores in laboratory examinations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(29 reference statements)
2
16
0
2
Order By: Relevance
“…Moreover, our findings concur with other investigators who revealed higher performance and information in intervention participants than control participants [18,28,32,[38][39][40]. Other studies documented significant improvement in students' achievement regarding clinical and critical thinking, decision making skills and self-confidence after SBL application [16,24,[41][42][43][44].…”
Section: Students' Achievementsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, our findings concur with other investigators who revealed higher performance and information in intervention participants than control participants [18,28,32,[38][39][40]. Other studies documented significant improvement in students' achievement regarding clinical and critical thinking, decision making skills and self-confidence after SBL application [16,24,[41][42][43][44].…”
Section: Students' Achievementsupporting
confidence: 90%
“…Two tools were used to collect data for the present study which was developed by the researcher based up on relevant literature. Tool one "Students' Achievement Sheet" [13,18,[24][25][26][27][28][29]35] that involved eight main domains. The first domain comprised 4 statements about analyzing the scenario.…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ] In this course, one of the most important learning needs is training of psychomotor skills that is done in the field of clinical skills lab. [ 2 ] Meanwhile, the students, especially in primary semesters, are in primary level of psychomotor skills. Hence, considerable time is allocated for attending the skills lab in this course.…”
Section: Introductionmentioning
confidence: 99%